SOCIO-ECONOMIC STATUS OF THE RURAL DAIRY FARMERS OF KAMRUP DISTRICT OF ASSAM (Indian Journal of Animal Production and Management, 2014)
An investigation was undertaken to evaluate the socio-economic status of the rural dairy farmers of Kamrup district of Assam with sample size of 200 dairy farmers. Seventy per cent of the respondents belonged to middle age category (36 years to 55 years) followed by young age category (35 years and below) and old age category (56 years and above) with 16.50 and 13.50 per cent respectively. The average age of the farmers was found to be 45 years. The majority (88%) of the respondents had medium sized family with 4-7 members followed by small sized family (3 members and below) and large sized family (8 members and above) with 6.50 and 5.50 per cent respectively. The majority of the farmers (83.50%) had medium level educational qualification from primary to higher secondary level followed by high level (11.00%) had low level (5.50%) educational qualification from graduate and above, and illiterate respectively. The annual family income of the dairy farmers ranged from Rs. 20,000.00 to Rs. 4,00,000.00. Majority of the dairy farmers (75.00%) had medium level annual family income from Rs. 19,467.88 to Rs. 1,21,230.12 followed by high level (25.00%) annual family income ranged from Rs. 1,21,230.13 and above.
Keywords: Socio-economic status; Age; Family size; Educational status; Annual income